Penerapan Metode MFCC dan LSTM untuk Pengenalan Emosi melalui Suara - Prawangsa, I Dewa Agung; Karyawati, Dr. Anak Agung Istri Ngurah Eka (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 4 (2024): JELIKU Volume 12 No 4, May 2024, 2024)
Speech recognition falls under the field of computational linguistics. This includes identification, recognition, and translation of speech detected into text by a computer. This research uses Mel Frequency Cepstral Coefficients (MFCC) and Recurrent Neural Networks (RNN) techniques as a form of Artificial Neural Networks (ANN) architecture. The main purpose of this research is to use speech recognition techniques to detect and identify various emotional sounds in a person. The MFCC process will convert the voice signal into several vectors that help for the speech recognition process in this study.